2014
DOI: 10.1111/aogs.12369
|View full text |Cite
|
Sign up to set email alerts
|

Scientific and clinical evidence for the use of fetal ECG ST segment analysis (STAN)

Abstract: Fetal electrocardiogram waveform analysis has been studied for many decades, but it is only in the last 20 years that computerization has made real-time analysis practical for clinical use. Changes in the ST segment have been shown to correlate with fetal condition, in particular with acid-base status. Metaanalysis of randomized trials (five in total, four using the computerized system) has shown that use of computerized ST segment analysis (STAN) reduces the need for fetal blood sampling by about 40%. However… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…11 It has also been suggested that there is a learning curve with ST-segment analysis. A reanalysis of the meta-analysis by Schuit et al showed that labor management with the use of ST-segment analysis reduced metabolic acidosis and adverse neonatal outcomes in the second half of the trials.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11 It has also been suggested that there is a learning curve with ST-segment analysis. A reanalysis of the meta-analysis by Schuit et al showed that labor management with the use of ST-segment analysis reduced metabolic acidosis and adverse neonatal outcomes in the second half of the trials.…”
Section: Discussionmentioning
confidence: 99%
“…However, the relevance of these results to usual obstetrical practice is unclear, given inconsistent findings among published trials and questions about eligibility criteria, choice and definition of primary outcomes, and intrapartum management, as discussed by Øian and Blix 10 and Steer and Hvidman. 11 Moreover, there are substantive differences between U.S. and European practices. We designed a large, multi-institutional, randomized trial to assess the effects of using fetal ECG ST-segment analysis on perinatal outcomes.…”
mentioning
confidence: 99%
“…However, the relevance of these results to usual obstetrical practice is unclear, given inconsistent findings among published trials and questions about eligibility criteria, choice and definition of primary outcomes, and intrapartum management, as discussed by Øian and Blix 10 and Steer and Hvidman. 11 Moreover, there are substantive differences between U.S. and European practices. We designed a large, multi-institutional, randomized trial to assess the effects of using fetal ECG ST-segment analysis on perinatal outcomes.…”
mentioning
confidence: 99%
“…53 Three cases of intrapartum metabolic acidosis were documented by the Dutch group 54 and a paper from St. George’s Hospital in London reported on 14 cases of neonatal encephalopathy in the first 1052 patients who were monitored using STAN and stated that in only 7 of these 14 had there been a significant ST event. 55 It was subsequently established that STAN monitoring was being started when the fetal heart rate tracing was already abnormal, a finding that reinforces the importance of only starting STAN monitoring after a reassuring pattern has been established (and maintained until the baseline ST analysis is completed).…”
Section: The Randomized Trials and Their Analysismentioning
confidence: 99%